Contribution of Regional anaesthesia on health economics: cost effectiveness of preemptive TAP block in Laparoscopic cholecystectomy - Azad, Salahuddin Al; Dutta, Mishuk; Nimmi, Nahida Parveen; Badruddoza, A N M; Mitra, S P; Islam, Azharul; Aziz, Lutful (Journal of the Bangladesh Society of Anaesthesiologists, 2020)
Objective: Regional anaesthesia can play a vital role as a supplement of general anaesthesia inlaparoscopic cholecystectomy surgery. In this study we postulated that preemptive bilateral dualtransversus abdominis plane (BD - TAP) block has the potential to reduce the requirement of volatileanaesthetic, muscle relaxant, postoperative opioid demand and shortening of hospital stay in laparoscopiccholecystectomy surgery, ultimately total cost. Method: Total 40 patients ASA I - II undergoing laparoscopic cholecystectomy surgery were randomlyassigned into two equal groups of 20 patients each. All patients received preemptive IV Paracetamol (15mg/kg), IV Diclofenac (1 mg/kg) and BD - TAP block. Block was performed with bilateral Subcostal(medial to linea semilunaris) and lateral TAP injection with total 70 ml drug volume. Group A receiveda drug solution containing plain Bupivacaine 15 ml (0.1%), Lidocaine 35ml (1%), Dexamethasone 10mg. Group B received a total 70 ml normal saline injection. Maintenance of anaesthesia was accomplishedwith low flow anaesthesia (0.5 - 1.0 L/min) accompanied by BIS monitoring, maintaining BIS index 45- 55. All patients received Sevoflurane with N2O 60%. Muscle relaxation was guided by TOF monitoringand supplemental dose was adjusted by the TOF counting. Postoperative analgesia was maintainedwith IM pethidine in p.r.n dose and oral paracetamol in regular doses. Total opioid requirement, musclerelaxant and volatile anaesthetic used and duration of postoperative hospital stay were recorded. Result: BD - TAP block reduced the Sevoflurane requirement, group A 5.5 (± 0.05) ml/ hr and group B6.8 (± 0.9) ml/ hr (p < 0.05). It also reduced the requirement of Rocuronium in comparison to controlgroup, group A 49.5 (± 2.85) mg and in group B 58 (± 4.21) mg (p < 0.05). Postoperative pethidinerequirement, group A 135 (± 22.9) mg and group B 375 (± 46) mg (p < 0.05). It also facilitated rapidhospital discharge, group A 1.16 (± 0.5) days and group B 2.03 (± 0.5) days (p < 0.05). Conclusion: In this study it is demonstrated that preemptive (BD - TAP) block in laparoscopiccholecystectomy surgery is associated with reduced requirement of volatile anaesthetic, muscle relaxantand postoperative opioid consumption. It seems that regional anaesthesia has a big contribution inmodern health economics and national health policy should consider this issue. JBSA 2020; 33(1): 3-9